2017
DOI: 10.18272/aci.v9i15.456
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary assessment of the degree of genetic diversity of Ecuadorean Ilex guayusa using inter simple sequence repeat (ISSR) markers

Abstract: Estudio preliminar de la diversidad genética de Ilex guayusa ecuatoriana mediante marcadores inter simple sequence repeat (ISSR) ResumenEvaluamos el grado de diversidad genética de Ilex guayusa, una especie de importancia etnobotánica y comercial para las comunidades indígenas de la Amazonía ecuatoriana. Caracterizamos genéticamente a 157 individuos, provenientes de chacras ubicadas a lo largo de seis provincias, con nueve marcadores ISSR (Inter Simple Sequence Repeats). Se detectó en total 91 bandas polimórfi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…In this study, we found that I. guayusa presents a moderately low genetic diversity (He = 0.396) in the Ecuadorian Amazon region. In a previous report, we assessed the preliminary genetic diversity of guayusa from the Ecuadorian Amazon using ISSRs markers and found that it was considerably lower than the one found with SSR markers (He = 0.19) [25]. Direct comparisons are not possible since the molecular markers used were different; however, the higher levels of genetic diversity found could be attributed to the high discriminating power of SSRs [79][80][81].…”
Section: A Moderately Low Genetic Diversity For Ilex Guayusa In the Ecuadorian Amazonmentioning
confidence: 94%
See 2 more Smart Citations
“…In this study, we found that I. guayusa presents a moderately low genetic diversity (He = 0.396) in the Ecuadorian Amazon region. In a previous report, we assessed the preliminary genetic diversity of guayusa from the Ecuadorian Amazon using ISSRs markers and found that it was considerably lower than the one found with SSR markers (He = 0.19) [25]. Direct comparisons are not possible since the molecular markers used were different; however, the higher levels of genetic diversity found could be attributed to the high discriminating power of SSRs [79][80][81].…”
Section: A Moderately Low Genetic Diversity For Ilex Guayusa In the Ecuadorian Amazonmentioning
confidence: 94%
“…[18], and I. aquifolium L. [19], among others [20][21][22], have been widely studied in terms of their genetic diversity and phytochemical composition [23,24]. In the case of guayusa, most research has focused on exploring its chemical properties and ethnobotanical uses [3,6,9], while information on genetics and cultivation history remains scarce [25]. Given that guayusa's primary strategy for reproduction is asexual and humanmediated, establishing its genetic status represents an interesting case study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation